Pengembangan Bahan Ajar Ekonomi Terintegrasi Ayat-Ayat Suci Al-Qur’an Dan Al-Hadist Pada Siswa Kelas X Di MA Darussholihin NW Kalijaga Lombok Timur - Ummah, Solihatun; Fahrurrozi, muhammad; Zain, Rohaeniah (JPEK: Jurnal Pendidikan Ekonomi dan Kewirausahaan, 2018)
This study aims to determine the steps of development of integrated economic teaching materials of the holy verses of al-qur'an and al-hadist to know the result of development of integrated economic learning materials of the holy verses of al-qur'an and al-hadist on class students X at MA Darussholihin NW Kalijaga. This research is a development research by adopting Borg & Gall development model, to 7 that is, requirement analysis, planning, early product format development, initial product validation, product revision, field trial, revision of final product of research subject is class X MA Darussholihin NW Kalijaga as many as 30 students. Data collected in this research is qualitative and quantitative data of data collection instrument include questionnaire of student response of technical analysis of data used in this research is static formula for validation of teaching materials. Based on validation results from material experts and high quality linguists with the number of expert material values 53 linguists 37 average score of 90% with a high or valid height. Student's response to teaching materials is very high with average percentage of 85.15% overall components in the range of 82% - 100% with very responding category.